INDIA’S “SOFT POWER” DURING N.MODI’S ADMINISTRATION (2014 – PRESENT) - Thi Thanh Huyen, Pham (Tạp chí Khoa học Trường Đại học Sư phạm Hà Nội: Khoa học Xã hội, 2025)
“Soft power” is now genuinely becoming vital for improving nations’ standing and clout. In that regard, India is likewise increasing its involvement in global affairs to expand its influence. India frequently opts for peaceful cultural dissemination because of its distinctive historical features. This strategy is essential for India to successfully market its cultural traits. This quality is seen as a potent weapon for India in expanding its soft power around the globe today. Prime Minister Narendra Modi makes full use of India’s unique cultural advantages. To date, the N. Modi government’s development and use of soft power has been a considerable success, drawing the attention of international leaders. The Modi government has opened up the dialogue between India’s soft power potential and its foreign policy. For the first time, the Indian government is beginning to methodically use rich human and cultural resources that have hitherto evolved independently of official policy. With an interdisciplinary approach, the article below discusses India’s soft power-building policies during Prime Minister Narendra Modi’s tenure (from 2014 to present), viewing them as one of the secrets to India’s remarkable transformation, assisting the country in establishing its position in the new global order.